Growth Effects of Mango Grafting (Mangifera Indica L.) Against gibberellin feeding in scion varieties - Suyani, Ida Sugeng; Hartanti, Aprilia; Florentina, Florentina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
Mango (Mangifera indica L.) is a fruit plant that has great development potential because of its high genetic diversity. Mangoes are popular for their delicious sweet taste once they reach maturity. This research aims to: 1) Find out the effect of giving gibberellin on the growth of Mangifera indica L. grafted seeds. 2) To determine the effect of growth of grafted mango plant seeds (Mangnivera indica L) on scion variants. 3) Find out whether gibberlin and scion varieties affect the growth of grafted mango (Mangifera indica L) seedlings. First hypothesis: 1. The growth of grafted mango plant seedlings (Mangifera indica L) is influenced by the use of gibberellin. 2) The scion variety influences the development of grafted mango plant seeds (Mangifera indica L). 3) The interaction of gibberellin and scion type influences the growth of mango (Mangifera indica L) seedlings after grafting. This study tested the effect of giving gibberlin at three levels and scion varieties at three levels of treatment using a factorial randomized block design (RAK) with two levels. Three copies of the experiment were carried out. The analysis will proceed to the least significant difference test (BNT) at a significance level of 5% if the F test findings show a statistically significant effect.